PEMBERDAYAAN PETANI DALAM MENERAPKAN PROGRAM SYSTEM OF RICE INTENSIFICATION (SRI) BERBASIS KEGIATAN KELOMPOK - Khoriri, Syaifurrizal; Subekti, Sri; Agustina, Titin (Universitas Sebelas Maret, 2018)
System of Rice Intensification (SRI) is one of the agricultural technology obtained from the extension program in improving the ability of farmers' cropping pattern on their farming. The purpose of this research is (1) to identify the empowerment of the SRI farmers and (2)to identify farmer group strategies in empowering farmers through the SRI program. The method used descriptive qualitative. The research area was done intentionally in barokah farmer group Rowotengah Village Sumberbaru District Jember Regency. The key informant were usingleader of farmer group with Agricultural Extension Farmer and the secondary informant were member of farmer group. The data was collected by using interviews, observation and documentation. The result of the research concluded that: (1) the ability of farmers in implementing SRI’s program conducted by (a) farmer of SRI program were based on farmers' choice due to production facilities support, see the success of the initial farmer, self-test results and the opportunities of barokah farmer group as the program recepient because of the potential land, irigation and the dynamics of farmers group, (b) farmers' ability to access farming needs in increasing production by transplanting of young seedling, transplanting of single seedling, wide plant spacing and compost application, (c) farmers' ability to complain in the case of snail attack and the rapid growth of grass, (d) farmers' ability to reach SRI's planting technology through farmer group functions, (e) improvement of farmer resource capability, and (f) farmers' ability to optimize the production facilities in increasing crop production and income. (2) The group's strategy of empowering farmers is done by a) motivating of rice planter by doubling wages, b) giving of materials and training on the land, c) group management on program planning, implementation and evaluation, d) mobilizing farmers to use hybrid seed, and e) improvement of farming using SRI planting equipment.